A Secure Cloud Based File Exchange System - Larsson, Erik (My University, 2012)
This thesis will present an approach on how to build a system to exchange files stored in the 'cloud', between two or more users in a secure way. At rest different attack vectors will be presented to inform the reader why different security measures are taken throughout the system. The system will later be described in a theoretical aspect and different security aspects will be argued for. Different solutions will be proposed and discussed to achieve the best possible solution. The actual programming implementation will not be covered in details, although different guidelines on how to program in a secure way will be discussed. At last the testing will covered. Both what can be done during the development phase but also different steps on how to test the final product. The thesis aim to show one way to build a cloud based web application to exchange data between users as secure as possible. The security will always be in focus, and other angles such as the overall user experience or time consumption for different solutions will not be considered in first hand.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Data- och systemvetenskap; Computer and Information Science; Information & Communication Technology; Computer and systems science